Precipitation analysis and water resource of Wadi Siham Basin, Yemen - Al Ward, Ahmed Majed (Tanjong Malim, 2019)
Precipitation analysis and water resource of Wadi Siham Basin, Yemen by Al Ward, Ahmed Majed